Price level targeting - Malik Shukayev; Alexander Ueberfeldt (Bank of Canada, 2010)
Various papers have suggested that Price-Level targeting is a welfare improving policy relative to Inflation targeting. From a practical standpoint, this raises an important yet unanswered question: What is the optimal price index to target? This paper derives the optimal price level targeting index defined over the eight main components of the Consumer Price Index. It finds that such an index places a heavier weight, relative to the expenditure weight, on sectors with slow price adjustments. However, using the expenditure weights instead of the optimal ones results in very small welfare cost.
Keywords: E32; E52; 330; Monetary policy framework; Geldpolitik; Inflation Targeting; Lebenshaltungsindex; Preisniveau; Statistische Methode; Wohlfahrtseffekt